2010
DOI: 10.1111/j.1439-0531.2009.01562.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Approaches to Pregnancy Loss of Non‐infectious Cause During the Late Embryonic/Early Foetal Period in Dairy Cattle. A Review

Abstract: The problem of pregnancy loss during the late embryonic/early foetal period due to non-infectious causes in dairy cattle is on the rise, especially in high milk producing cows. This review discusses recent therapeutic approaches designed to reduce the incidence of early foetal loss. These strategies are based on the fact that low plasma concentrations of progesterone are commonly related to foetal loss. Progesterone supplementation during the late embryonic/early foetal period has proven useful in curtailing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 98 publications
(117 reference statements)
0
6
0
Order By: Relevance
“…This agrees with literature from the past 20 years, where occurrence of pregnancy loss persistently peaks during the first three months of pregnancy. [10][11][12] A particular study shows for instance, that over 90% of fetal losses in dairy cattle in Spain, calculated from pregnancy diagnosis at day 30 postinsemination, occur before day 90 of gestation. 11 It is important to note that initial gestational age should be considered when calculating the abortion index, since early embryonic or fetal deaths can go unnoticed when methods for pregancy diagnosis of such as rectal palpation are used (between days 45 and 50 of gestation).…”
Section: Resultsmentioning
confidence: 99%
“…This agrees with literature from the past 20 years, where occurrence of pregnancy loss persistently peaks during the first three months of pregnancy. [10][11][12] A particular study shows for instance, that over 90% of fetal losses in dairy cattle in Spain, calculated from pregnancy diagnosis at day 30 postinsemination, occur before day 90 of gestation. 11 It is important to note that initial gestational age should be considered when calculating the abortion index, since early embryonic or fetal deaths can go unnoticed when methods for pregancy diagnosis of such as rectal palpation are used (between days 45 and 50 of gestation).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, as GnRH treatment at pregnancy diagnosis in cows carrying twins favors pregnancy maintenance (Bech-Sàbat et al, 2010;, the effects of a double GnRH dose on pregnancy survival in twin pregnancies was recently investigated . However, in high producing dairy cows carrying twins, a single or double GnRH dose given at pregnancy diagnosis returned similar pregnancy loss rates and reduced the risk of pregnancy loss up to three times compared to untreated cows .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that GnRH or hCG treatment applied at the time of pregnancy diagnosis (i.e., 28–40 days) has no apparent effect on the subsequent pregnancy loss rate in cows carrying singletons [13] or other pregnancy types [14, 15]. However, it has been established that GnRH treatment in cows carrying twins favors pregnancy maintenance [6, 16]. In a previous study, it was found that GnRH treatment promoted twin reduction compared to progesterone-based treatment, but this study did not include untreated control cows [13].…”
mentioning
confidence: 99%